Prevalence and Molecular Characteristics of Extended-Spectrum and AmpC β-Lactamase Producing Escherichia coli in Grazing Beef Cattle - Lee, Shinyoung; Teng, Lin; DiLorenzo, Nicolas; Weppelmann, Thomas A.; Jeong, Kwangcheol Casey (Frontiers in Microbiology, 2020)
The emergence of extended-spectrum β-lactamase (ESBL) and AmpC β-lactamase producing E. coli represent a contemporary public health threat. ESBL and AmpC β-lactamase genes translocate between chromosomes and plasmids, facilitating rapid spread throughout the environment. In this study, ESBL/AmpC producing bacteria were isolated from beef cattle farms with seldom antibiotic use. Eleven farms out of 17 tested, had ESBL/AmpC producing E. coli in animals, soil, and forage samples. Fifty-nine CTX-M or CMY-2 positive E. coli isolates were further characterized with whole-genome sequencing. The isolates commonly carried CMY-2, TEM, or CTX-M genes, and over half encoded both CTX-M and TEM genes. Using comparative genomics, antibiotic resistance genes from 12 classes of antibiotics were identified and confirmed by antibiotic susceptibility test, revealing multidrug resistance against multiple classes of antibiotics. Virulence factors related to adherence, invasion, iron uptake, and bacterial secretion systems were shared by all isolates; some of which were identified as enteropathogenic E. coli. Phylogenetic analyses revealed a pattern of close genetic relatedness, suggesting that ESBL/AmpC producing E. coli were transmitted among farms as well as independent evolution within farms. Our results indicate that ESBL and AmpC β-lactamases prevail in food animal production system regardless antibiotic use and have the characteristics for zoonotic transmission.